Joint ventures in the P. R. China - Wolfgang Klenner; Kurt Wiesegart (Intereconomics, 1980)
China is showing interest in joint ventures in the oil, coal and nonferrous metals sector, in electricity generation, steel and building materials production, in the mechanical engineering, textile and electrical industries, in the transport sector and in the hotel trade. Our article gives an outline of the problems which the future joint ventures in China will encounter.
Keywords: 330; China